TINJAUAN TEORI LITERASI KONTEN KAMPANYE GRACE NATALIE DI INSTAGRAM PADA MAHASISWA ILMU KOMUNIKASI - Hakim, Lukman; Sutjipto, Vera Wijayanti (Universitas Muhammadiyah Jember, 2020)
Grace Natalie Lousia is a chair of PSI . In winning the 2019 general election, strategies are needed, one of which is a campaign strategy through social media. The purpose of this research is to find out whether the campaign carried out by Grace Natalie on Instagram social media is successful if viewed from the literacy ability of her Instagram media content on Communication Studies students at Universitas Negeri Jakarta. The theory of this research is the theory of Media Literacy. The type of this research is quantitative with a population of 121 and a total sample of 93 Communication Studies students at the Universitas Negeri Jakarta based on the calculation of the Yamane formula. Researchers used a questionnaire instrument in gathering data for this study. The results of this research conclude that the level of media content literacy for Grace Natalie's campaign content on social media Instagram is quite good in society. The better the level of media literacy in Grace Natalie's campaign content, the higher the level of effective use of social media to serve as a campaign venue.